2014
DOI: 10.4236/ojanes.2014.47023
|View full text |Cite
|
Sign up to set email alerts
|

Epidural Hematoma after the Use of Subcutaneous Unfractionated Heparin and History of Epidural Tumor

Abstract: The patient was a 66-year-old male with a history of renal cell carcinoma with metastasis to the L2, L3, and L4 vertebral bodies scheduled for a radical nephrectomy and adrenalectomy. Prior to surgery the patient had undergone 10 radiation treatments for the vertebral metastasis. Patient medications included colace, prednisone, ibuprofen (taken 4 days prior to procedure), sunitinib, hydrocodone, benazepril, nexium, rosuvastatin, allopurinol, and azor. Physical exam prior to surgery was normal with no focal fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…At the same time, this study also found that there was no correlation between HEP and EPO levels, which was consistent with our previous research results [10][11][12]. This is because HEP is an important factor leading to anemia in tumors or other chronic inflammatory diseases.…”
Section: Discusssupporting
confidence: 92%
See 1 more Smart Citation
“…At the same time, this study also found that there was no correlation between HEP and EPO levels, which was consistent with our previous research results [10][11][12]. This is because HEP is an important factor leading to anemia in tumors or other chronic inflammatory diseases.…”
Section: Discusssupporting
confidence: 92%
“…Existing studies both native and foreign have shown that inflammatory mediators, especially HEP, play an important role in the occurrence and development of tumor-related anemia [12]. In this study, it was found that HEP decreased gradually with the aggravation of anemia (i.e.…”
Section: Discussmentioning
confidence: 53%
“…For example, unfractionated heparin may have placed the patient at an increased risk for an epidural hematoma. This is especially prudent in the setting of TID-dosed subcutaneous heparin [12].…”
Section: Discussionmentioning
confidence: 99%